Analysis of Digital Signal Processing Algorithms Based on Vedic Mathematics - Lisha, A; Monoth, T (International Journal of Computer Sciences and Engineering, 2025)
India has a rich intellectual tradition that evolved since last 5000 years. To our luck much knowledge acquired over this period were kept as ancient scriptures. Vedic Mathematics is the name given to the ancient system of Indian Mathematics which was rediscovered from the vedas by Sri Bharathi Krishna Tirthaji. The whole vedic mathematics is based on sixteen sutras providing unique and simple techniques to various mathematical computations. Processing time, power and hardware are the main challenging aspects in any computer algorithms. Hence high speed mathematical tools are of great demand. Ancient Indian scripts are believed to contain many mathematical shortcuts which can be used to fine-tune computer algorithms. Many researchers found the Vedic multipliers, adders and other vedic tools help in saving resources. In this paper we present various applications of vedic mathematics in Digital Signal Processing and also analyzed computational complexity of various algorithms in digital signal processing using vedic mathematics proposed by different researchers